Navigation-Assisted One-Stage Total Knee Arthroplasty With Extra-Articular Corrective Osteotomy for Knee Osteoarthritis With Femoral and Tibial Extra-Articular Deformity: A Case Report - Mitsuhiko Kubo; Sho Hirobe; Tsutomu Maeda; Kosuke Kumagai; Yasutaka Amano; Yuki Nosaka; Takahide Hasegawa; Shinji Imai (Case Reports in Orthopedics)
Conclusions: One-stage TKA with extra-articular corrective osteotomy achieved good clinical results due to accurate alignment using navigation and firm fixation of the osteotomy site using cemented-stem and metaphyseal sleeve without any fixation devices.